Determinan Carbon Emission Disclosure Perusahaan Manufaktur - Dewi, Luh Gede Krisna; Yenni Latrini, Made; Rsi Respati, Ni Nyoman (E-Jurnal Akuntansi; Vol 28 No 1 (2019), 2019)
Company activities has role in increasing the levels of gas carbon in the atmosphere . Accounting practises assesed by several parties as the trigger for the environmental crisis. As the response, the company began to pay more attention to the effort of the carbon emissions reduction and conduct comprehensive disclosure associated with it. R esearch uses mutiple regression analysis to seek the effect of economic, social, financial market, and regulatory pressure on the carbon emission disclosure of manufacturing companies listed on the BEI. The result of the data analysis discover that regulatory pressure  was able to influence carbon emission disclosure of manufacturing company. While the pressure factor comes from economic, social and financial market has no effect on the area of carbon emission disclosure. The implication of this research become an input for the standard setter in compiling and policies evaluation process with voluntary disclosure in the company’s financial report. Keywords: Carbon emission disclosure, economic, social, financial market, regulatory pressur